Granito São Francisco e formação Serra da Bocaina : evidências de magmatismo orosiriano em arco magmático continental : terreno Rio Apa - Sul do Cráton Amazônico - Souza, Cinthya de Deus (2016)
The Sao Francisco Granite and Serra da Bocaina Formation are located in the southernmost part of the Amazon Craton - near the boundaries between Brazil-Bolivia- Paraguay, southeast of the Brazilian state of Mato Grosso do Sul, Porto Murtinho City, which is partially covered by Quaternary sediments of the Pantanal Formation and Alluvial Deposits. Two petrographic facies have been identified in the Sao Francisco Granite based on geological mapping and petrographic analysis: Biotite Monzo to Syenogranite and Alkali-feldspar Graphic Granite. The former occurs only in the NE and SE of the study area being composed of pink to greenish gray medium-grained leucocratic rocks which shows inequigranular hypidiomorphic to xenomorphic textures. The latter is the dominant rock type in the batholith being composed of pink to reddish porphyritic fine- to medium-grained leucocratic rocks with hypidiomorphic texture as well as micrographic (granophyric) intergrowths. Two deformation stages are observed: a ductile-brittle stage (F1) and a brittle stage (F2). The rocks of the Sao Francisco Granite are hosted by volcanic rocks of the Serra da Bocaina Formation as highlighted by the intrusion of dykes and apophyses. The Serra da Bocaina in the Sao Francisco Hill results from effusive volcanism according to concordant subaerial volcanic deposits that occur in the form of rhyolitic lava, but it is also attributed to explosive volcanism due to the occurrence of ignimbrite deposits that are here divided into three petrographic facies: Lithic Ignimbrite, Crystal-rich Ignimbrite and Ignimbrite Tuff. In the study area, xenoliths of tremolite-actinolite schist belonging to the Porto Murtinho Complex, which composes the basement rock, are identified. Geochemical data from the Sao Francisco Granite and volcanics of the Serra da Bocaina Formation show that these rocks are of acid composition with magmatism emplacement in magmatic arc settings; in post collisional stage, data also yield ferroan and peraluminous affinities which are compatible with A-type granites. U-Pb zircon (SHRIMP) analyses yield crystallization ages of 1878 ± 7 Ma for the Sao Francisco Granite, and 1899 ± 4 Ma for the rhyolitic flows of Serra da Bocaina Formation. Whole-rock Sm-Nd analyses yield εNd(1,87 Ga) negative values ranging from -3.65 to -2.53, and TDM ages 2.60 and 2.36 Ga that indicate these rocks must have formed by partial melting of continental crust. The results show that the Sao Francisco Granite and the volcanics of the Serra da Bocaina Formation are related to an Orosirian plutonic and volcanic event which is attributed to the Amoguija Magmatic Arc.